Activation of MnIIMnIII-Peroxides with Relevance to the Catalytic Cycle of Ib RNRs - Doyle, Lorna (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2023)
The understanding of the catalytic cycle of Ib ribonucleotide reductases (RNRs) has been hindered by the inability to trap the species formed following reaction of superoxide (O2-) and the MnII2 active site. This unknown intermediate rapidly converted to a bis(?-oxo)MnIIIMnIV species and oxidised a nearby tyrosine residue to a tyrosyl radical, that was responsible for initiating ribonucleotide reduction. Studying the structure and reactivity of species formed during reaction of biomimetic MnII2 complexes with O2- may provide some insight into the unknown intermediate in the enzymes catalytic cycle and this was the main objective of this thesis. The main topics of this thesis was the preparation, characterisation, and study of the reactivity of MnIIMnIII-peroxide species as mimics for the unknown intermediate in Ib RNRs. In chapter 2, upon reaction of O2- with [MnII2(OCCH3)2(BPMP)](ClO4) (1) , where HBPMP = 2,6-bis{[(bis(2-pyridylmethyl)amino]methyl}-4-methylphenol), the previously published [MnIIMnIII(O2)(BPMP)]2+ (2) was generated. 2 was characterised using UV-vis, EPR, XANES, and ESI-MS techniques. The yield of 2 was optimised upon substitution of the chelating agent 18-crown-6 with 222-Cryptand. 2 was capable of performing aldehyde deformylation of the substrates PPA and CCA. 2 was found to undergo a two-step mechanism during the reaction with aldehydes undergoing an initial reversible nucleophilic attack of the aldehyde by 2 followed by a Criegee rearrangement. In order to understand the role of the proton in the catalytic cycle of Ib RNRs, the reactivity of 2 towards acids was investigated. Addition of the strong acid HCl to 2 resulted in the formation of a MnIIMnIII species (3) observed by UV-vis spectroscopy and the postulated evolution of H2O2. Attempts to characterise 3 using EPR spectroscopy were unsuccessful due to the formation of ?free? MnII ions that saturated the EPR spectrum. Addition 2 eq. of the weak acid pTsOH to 2 resulted in the generation of a new species (4) as evidenced by the formation of new electronic absorption features (?max = 550 nm). New species 4 was further characterised using EPR and X-ray absorption spectroscopies and mass spectrometry and determined to be a new bis(?-oxo)MnIIIMnIV species. Base reactivity studies with 4 indicated that a proton may reside on the bis(?-oxo) core of the complex. Using EPR spectroscopy, 4 was found to be capable of the one-electron oxidation of 4-methoxy-2,6-di-tert-butylphenol, a functional mimic for the tyrosine residue in Ib RNRs. Further kinetic analysis of the reaction of 4 with O-H bond containing substrates determined that 4 was reacting via a HAT mechanism. In chapter 4, upon warming of 2 a new species (5) was generated as evidenced by the formation of a new broad, featureless electronic absorption feature. Characterisation of 5 via EPR, XAS, and ESI-MS studies determined it to be a new bis(?-oxo)MnIIIMnIV species. Base studies on complex 5 indicated it contained a ?naked? bis(?-oxo) core, in contrast to the previously characterised 4 in which similar base studies implied the presence of a proton on the bis(?-oxo) core. 5 was also found capable of the one-electron oxidation of 4-OMe-2,6-DTBP to the corresponding phenoxyl radical species by EPR spectroscopy. In the reaction of 5 with para-substituted phenols 5 displayed saturation kinetics indicative of the reversible formation of an intermediate prior to phenol oxidation. We postulated the source of the saturation kinetics was the initial association of the O-H bond of the phenol to the bis(?-oxo) core which activated the core towards oxidation of the phenol. We speculated that without this initial association step the MnIIIMnIV was not reactive enough to oxidise O-H bonds. This was consistent with the observation of linear mechanism in the oxidation of O-H bonds by 4, which we postulated contained a proton on the bis(?-oxo) core. This proton increased the electrophilicity of 4 and negated the requirement for the association step required for activation. Further kinetic analysis of the reaction of 5 with O-H bond containing substrates determined 5 was reacting via HAT mechanism with O-H bond substrates. Sc(OTf)3 was added to 2 to investigate the effect in utilising Lewis acids sources as a means to activate the MnIIMnIII-peroxide. Addition of 1 eq. of Sc(OTf)3 to 2 generated a new species 6 with electronic absorption features at ?max = 410 and 550 nm. EPR, XANES, and ESI-MS analysis of 6 determined it to be a new bis(?-oxo)MnIIIMnIV species. Further EPR analysis found that 6 was capable of the one-electron oxidation of 4-OMe-2,6-DTBP to the corresponding phenoxyl radical. Kinetic analysis of the reaction of 6 with 4-OMe-TEMPO-H established that 6 reacted via a linear mechanism. Interestingly, comparison of the k1 values calculated for the reaction of 4 and 6 with 4-OMe-TEMPO-H under the same conditions revealed that 6 reacted four-times faster than 4. We postulated that the source of the increased rate was due to a Sc3+ ion associated with the core of 6. As Sc3+ was a stronger Lewis acid than H+ its presence in 6 resulted in a more electrophilic core and greater reactivity compared to complex 4. This also provided further weight to the argument that the source of the saturation kinetics of 5 is due to the ?naked? bis(?-oxo) core. Finally, in chapter 6 a new MnII2 complex ([MnII2(TPDP)(O2CC6H5)2](BPh4) = 7) was synthesised and characterised using XRD, IR, NMR, XANES, and mass spectrometry techniques and was found to contain two MnII2 centres ligated by TPDP and two benzoic acid moieties. Reaction of 7 with O2- resulted in the formation of a new species (8) with electronic absorption features very similar to that of 2 at ?max = 450 and 590 nm. 8 was characterised using EPR, XAS, Raman, and mass spectrometry techniques and assigned as a new MnIIMnIII-peroxide species. 8 was, to the best of our knowledge, only the third of its kind to be characterised in the literature. The reactivity of 8 was explored and the MnIIMnIII-peroxide did not react with O-H bonds determined to be poor electrophile. Addition of 2 eq. of pTsOH to 8 resulted in the formation of a new MnIIMnIII-hydroperoxo species (9) as evidenced by UV-vis, EPR, and XANES methods. 9 was found to be capable of the oxidation of the O-H bond of TEMPO-H via EPR spectroscopy. This was an interesting result as 8, the precursor complex to 9, displayed no reactivity with the same substrate under the same conditions. Despite this, the reaction of 9 and TEMPO-H was sluggish and afforded only modest yields of the TEMPO? radical.
APPROVED
Keywords: Ribonucleotide Reductase; Manganese; Electronic Paramagnetic Resonance; Biomimetic Chemistry; Bioinorganic Chemistry